TELESSAÚDE e educação permanente em saúde: uma revisão integrativa - Santos, Cassia Glauciene Clementino Sales dos [UNIFESP] (2020)
INTRODUCTION: TELESSAÚDE (TELEHEALTH) is understood as the use of communication for distance activities, which uses health-related information technologies at the primary, secondary and tertiary levels, and enables access to diagnostic and / or therapeutic support resources among health professionals or between them and their patients and users. Within SUS, TELESSAÚDE is committed to two priorities: health education and the provision of secondary care. OBJECTIVE: to analyze how the relations between TELESSAÚDE and Permanent Health Education have been discussed in scientific articles published from 2007 to 2018. METHOD: an integrative review covering publications found in the period from 2007 to 2018, based on the question: how does the scientific literature describe the tools of innovation, technology and information (TELESSAÚDE) and possible connections with the teaching-learning processes in the Permanent Education of professionals in SUS? The search and capture comprised articles published in the Virtual Health Library - VHL, Medline, SCIELO and LILACS databases, considering the descriptors TELESSAÚDE and Permanent Education in Health. The data production process was carried out between October 2019 and March 2020 The inclusion criteria included manuscripts that are original articles, published and indexed in the referred databases, in Portuguese, English and Spanish. RESULTS AND DISCUSSION: from the searches performed and considering the criteria adopted in this research, an empirical field of 17 articles was configured for analysis. Among the total of articles, 16 were found to be produced in Brazil (notably in the Southeast Region), and only 01 was produced in the USA. Within the scope of the publication vehicles, a dispersion among the journals was identified with a maximum of three articles found in the same journal. With regard to methodological designs, it was possible to identify a predominance of qualitative studies, and the tools of TELESSAÚDE emerging linked to the processes and instruments inserted in the field of Information and Communication Technologies (ICTs) and Distance Education (EAD). TELESSAÚDE's connections with the continuing education processes of professionals in SUS were perceived as effective possibilities. These possibilities face limits to be overcome with emphasis on the lack of structure in the Health Services (covering equipment, materials, network and connectivity speed), HR, in particular, IT professionals) and the expansion of the number of tutors. FINAL CONSIDERATIONS: TELESSAÚDE is recognized as a critical, interactive and potentially transformative formative space that addresses the concept of Permanent Health Education as a dialogical process. From the research, the Infográfico TELESSAÚDE e Educação Permanente em Saúde: vamos conversar?( Infographic TELEHEALTH and Permanent Education in Health: shall we talk?) was elaborated. The referred products are expected to contribute to the enhancement of TELESSAÚDE in the processes of permanent education of health workers.